The prophet hud and the storm: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story recounts the life of Prophet Hud, who called his people to worship Allah and abandon their wrongdoing. It highlights his unwavering faith during a great storm sent as a warning, illustrating themes of patience, perseverance, and the consequences of ignoring divine guidance. Through Hud$1 (Bs example, children learn about the importance of faith and obedience to God.s